2016
DOI: 10.1001/jamaoncol.2015.6326
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis for PD-L1 Expression in Squamous Cell Carcinomas of the Cervix and Vulva

Abstract: Recurrent copy number gain of the genes encoding the PD-1 ligands provides a genetic basis for PD-L1 expression in a subset of cervical and vulvar SCCs and identifies a class of patients that are rational candidates for therapies targeting PD-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 15 publications
2
97
4
2
Order By: Relevance
“…Howitt et al have investigated the status of genes encoding PD-1 ligands in cervical SCC. They have found co-gain or co-amplification of CD274 and PDCD1LG2, coding PD-L1 and PD-L2, in a significant number of cervical SCCs [36]. In a recent study of cervical SCC, patients with diffuse expression of PD-L1 were also found to have significantly worse disease-free and disease-specific survival as compared to those with only marginal PD-L1 expression [10].…”
Section: Discussionmentioning
confidence: 99%
“…Howitt et al have investigated the status of genes encoding PD-1 ligands in cervical SCC. They have found co-gain or co-amplification of CD274 and PDCD1LG2, coding PD-L1 and PD-L2, in a significant number of cervical SCCs [36]. In a recent study of cervical SCC, patients with diffuse expression of PD-L1 were also found to have significantly worse disease-free and disease-specific survival as compared to those with only marginal PD-L1 expression [10].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a genetic analysis of Howitt et al [63] identified the rational candidates who may benefit from therapies targeting PD-1 in cervical or vulvar squamous cell carcinoma (SCC) based on the expression of PD-L1. They suggested that alteration of 9p24.1 gene copy number results in increased PD-L1 expression in cervical and vulvar SCC.…”
Section: Immunotherapy Editing Immune System By Reengineering T-cellsmentioning
confidence: 99%
“…To date, such amplifications have only been detected in small studies of head and neck squamous cell carcinoma, 14 cervical squamous cell carcinoma, 15 triple-negative breast cancer, 16-18 and non-small cell lung cancer. 19 Consistent with the aforementioned data on lymphomas, recent case reports found responses to PD-1 blockade in patients with PDL1 -amplified, microsatellite-stable colon cancer 20 and metastatic basal cell carcinoma, 21 suggesting the need for further interrogation of the potential utility of PDL1 amplifications as a biomarker for immune checkpoint blockade response.…”
mentioning
confidence: 99%